Lactobacillus plantarum CIDCA 8327: an α-glucan producing-strainisolated from kefir grains - Gangoiti, María Virginia (2017)
Lactobacillus plantarum CIDCA 8327 is an exopolysaccharide (EPS)-producer strain isolated from kefir withpromising properties for the development of functional foods. The aim of the present study was to char-acterize the structure of the EPS synthesized by this strain grown in skim milk or semidefined medium(SDM). Additionally, genes involved in EPS synthesis were detected by PCR. L. plantarum produces anEPS with a molecular weight of 104Da in both media. When grown in SDM produce an heteropolysac-charide composed mainly of glucose, glucosamine and rhamnose meanwhile the EPS produced in milkwas composed exclusively of glucose indicating the influence of the sugar source. FTIR spectra of thisEPS showed signals attributable to an a-glucan. Both by1H NMR and methylation analysis it was pos-sible to determine that this polysaccharide is a branched α-(1 → 4)-d-glucan composed of 80% linear α-(1 → 4)-d-glucopyranosyl units and 19% (1 → 4)-d-glucopyranosyl units substituted at O-3 by single α-D-glucopyranosil residues.